PELATIHAN BISNIS ONLINE UNTUK SISWA SMA: MENUMBUHKAN SEMANGAT WIRAUSAHA DIGITAL - Gultom, Angga Wibowo; Tusri, Yudi; Wulanda, Nourma; Shofia, Alima; Kurniawan, Anton (Gapenas Publisher, 2025)
Online Business Training for High School Students: Fostering the Spirit of Digital Entrepreneurship aims to provide understanding and skills in online business to the 12th-grade students of SMA Negeri 4 OKU, who are about to graduate. The issue addressed in this study is the lack of understanding among students about digital entrepreneurship and the lack of skills in managing online businesses. This research uses a direct training method with topics on the basics of online business, using e-commerce platforms, and digital marketing strategies. The results of the community service activities show that after attending the training, most students experienced an increased understanding of online business and felt more confident to start their own digital ventures. Qualitative analysis indicates that students felt more motivated and had a more positive outlook on entrepreneurship after gaining practical knowledge about online business. Additionally, there was a shift in students' mindset towards viewing digital business opportunities as a viable career alternative after graduation. This training successfully fostered the spirit of digital entrepreneurship among students and had a positive impact on their readiness to enter the workforce or become entrepreneurs